The Effectiveness of Principal Supervision in Increasing Elementary School Teachers' Work Motivation - Yenni Yenni; Rifma Rifma; Sulastri Sulastri (Suluah Pasaman, 2026)
Principal supervision is a strategic pillar in building teacher professionalism, but its effectiveness on teacher work motivation in elementary schools in rural areas has received little attention in the educational management literature. From an Islamic perspective, supervision is a manifestation of the values ​​of amanah and muraqabahbthe awareness of carrying out the responsibility of guidance before Allah SWT. This study aims to analyze the effectiveness of principal supervision and its relationship to the work motivation of public elementary school teachers in Koto Balingka District, West Pasaman Regency, using a quantitative approach with a descriptive correlational design. The population was 187 teachers from 14 public elementary schools, with a sample of 65 people determined using the Slovin formula and proportional random sampling. Data were collected using a Likert questionnaire that had been tested for validity and reliability, analyzed using descriptive statistics and Pearson correlation. The results showed that the effectiveness of supervision was in the fairly good category (mean = 3.12), with the feedback and follow-up dimension as the weakest point (2.91). Teacher work motivation was also quite good (3.27), with intrinsic motivation (3.47) higher than extrinsic motivation (3.06). There is a strong and significant positive relationship between the two variables (r = 0.612; p = 0.000; r² = 37.5%). This finding underscores the importance of strengthening supervisory competencies based on tarbiyah and ihsan values, particularly in areas with limited resources